Exploring the Factors Responsible for Gun and Knife Violence Among the Young Generation in the UK: A Scoping Review - White, Marie; Vinnakota, Divya; Hussain, Remsha; Sivasubramanian, Madhini (Asian Journal of Public Health and Nursing, 2024)
Background: Youth violence is the fourth leading cause of death among individuals aged 10-29, representing a significant global public health concern. In the UK, gun and knife crimes among youth are particularly troubling. This scoping review aims to identify the contributing factors of gun and knife violence among young people in the UK and their impact on mental health. Method: We searched literature using Medline, PubMed Central, Sunderland Library, Google Scholar, CINAHL, and approved government websites. Boolean operators were used with specific search terms, including only full-text, English-language, and original research publications. The PRISMA flowchart was used to document the selection process. Result: Out of 648 identified articles, 11 met the inclusion criteria. Three primary themes emerged: socio-economic factors, gang involvement, and mental health. Conclusion: Gun and knife violence among young people in the UK poses a significant public health burden. Effective interventions require addressing socio-economic disparities, preventing gang involvement, and providing accessible mental health support.